Childhood Obesity: Examining New Approaches to Tackle This Growing Health Concern - Agrawal , Amit; Agrawal, Rashmi; Shrivastava, Jyotsna (Indian Journal of Child Health, 2025)
The escalating prevalence and severity of obesity-related comorbidities in the pediatric population globally underscore the critical importance of addressing childhood obesity. Effective treatment strategies necessitate a thorough assessment of predisposing risk factors, which are characterized by a complex interplay between physical and environmental determinants. While extensive literature addresses adult obesity, a notable paucity exists regarding childhood obesity, highlighting an urgent research imperative. This review aims to comprehensively examine childhood obesity by identifying its underlying causes, exploring current diagnostic methodologies, and outlining effective management approaches. Given the increasing prevalence of this condition, the development and implementation of both individual and community-based interventions are crucial for achieving optimal prevention and management outcomes.